Using Primo Search Logs to Improve User Services - Coleman, Jason; Greene, Mira E. (My University, 2016)
Using search logs to customize Primo responses to user needs, Greene and Coleman discovered patterns of information seeking which lent itself to configurations to help with the discovery experience, make customizations that could possibly improve the user experience, and measure the impact of the customization.  In this will include discussion and conclusions drawn about the first customization which is meant to improve requests for interlibrary loan.
Citation: Coleman, Jason & Greene, Mira. (2016). Using Primo Search Logs to Improve User Services. Education and Behavioral Sciences Section, Research Committee Poster Forum, American Library Association Annual Conference, Orlando, FL.
Keywords: Primo; Information Seeking; Discovery; User Experience; Interlibrary Loan; Search Logs